Ham and belly processing characteristics of immunological castrated barrows (Improvest) fed ractopamine hydrochloride (Paylean). (February 2016) - Lowe, B.K.; Overholt, M.F.; Gerlemann, G.D.; Carr, S.N.; Rincker, P.J.; Schroeder, A.L.; Petry, D.B.; McKeith, F.K.; Allee, G.L.; Dilger, A.C.
Abstract: Effects of sex class (physically castrated, PC or immunologically castrated, IC) and diet (0 or 5 mg/kg ractopamine hydrochloride, RAC) on characteristics of ham and bellies were determined from pigs slaughtered in three groups with similar ending live weights. One carcass per pen per marketing group (n = 8) was selected to evaluate further processing characteristics. Data were analyzed as a 2 × 2 factorial design with a split plot in time and fixed effects of sex, diet, marketing group, and their interactions. IC fresh bellies were thinner ( P  < 0.01) and softer ( P  < 0.01) than PC bellies. IC hams and bellies were leaner ( P  < 0.05) than those from PC pigs. RAC feeding did not affect ( P  > 0.05) fresh ham or belly characteristics but decreased ( P  < 0.01) fat in cured PC bellies. Marketing group affected ( P  < 0.05) fresh quality, processing characteristics, and composition of hams and bellies. Immunological castration and RAC produced leaner finished products but did not alter processing yield of hams or bacon.